Topology Optimization of Flexible Multibody Systems Using Equivalent Static Loads and Displacement Fields. Issue 1 (December 2014) - Moghadasi, Ali; Held, Alexander; Seifried, Robert
Abstract Topology optimization techniques are applied in most cases for static applications. However, recently topology optimization procedures for structures under dynamic loads have been the focus of several studies. In this work, a topology optimization scheme for flexible multibody systems using equivalent static loads and displacement fields is investigated. The optimization problem is formulated using a homogenization method, more precisely, the solid isotropic material with penalization (SIMP) approach. The objective function in the optimization problem is the compliance and the method of moving asymptotes is used as optimizer. The objective function and the sensitivities are computed directly from the displacement field computed in the dynamic simulation. The examples of a 2‐arm manipulator and a slider‐crank mechanism are presented and the results are discussed to verify the improved dynamical behavior through this optimization method. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)